Aging, financing, and innovation in the health care system: a necessary discussion to maintain the right to health - Nossa, Paulo Nuno (Saúde e Sociedade, 2020)
This article discusses the safeguarding of the right to health, within the scope of a set of constitutional rights, materialized by public policies that organize the National Health Service in Portugal. Before the degradation of supply terms, frequently based on an association that observes the demographic aging as enough condition to justify the increase in health costs, legitimizing consequent restrictions on the supply. We conduct a literature review to search for factors that validate this association, examining arguments to understand this process; debating the validity of prospecting health costs using age-based models versus predictive models that consider the time to death. Additionally, we analyze the evolution of the main causes of mortality in Portugal between 1990 and 2017 for the groups 50-59 years and ≥70 years, causes of disability, as well as the prospects for public health financing in the percentage of GDP in countries of the Organization for Economic Cooperation and Development by 2030, while urgent and necessary solutions for Health Systems are considered, so they can gain efficiency without degrading performance, contributing and investing in a necessary co-responsibility in health on the demand side.